Importance of Circumferential Resection Margin in Management of Esophageal Cancer - Thakur, Binay; Devkota, Mukti; Aiming, Li; Pun, Ashis; Chaudhary, Manish (Nepalese Journal of Cancer, 2020)
Esophagectomy (R0) remains the gold standard for the management of esophageal cancer. But due to close vicinity of esophagus with the major structures like heart, aorta, vertebral column, tracheobronchial tree and lungs, a wider circumferential resection is generally not possible and a R1/ R2 resection might occur. Therefore, locoregional recurrence rates of esophageal cancer are reported to be as high as 52%. The Royal College of Pathologists (RCP) and The College of American Pathologists (CAP) define circumferential resection margin (CRM) differently. A mean overall CRM involvement was found to be 40.7% (RCP criteria) and 11.8% (CAP criteria). Twometa-analyses have shown poor survival in CRM positive cases. CRM positivity in T1/ T2 lesions should not occur unless there is a surgical fault. For T3 lesions, a higher rate of CRM positivity has been documented. Therefore, a wider CRM using transthoracic approach appears mandatory, especially for T3 lesions.